Mid-trimester sFlt-1/PlGF ratio and uterine artery Doppler for predicting preeclampsia in congenital uterine anomalies: a prospective cohort study - Felicia Sari; Agnes Mariska; Irna Nettles (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Congenital uterine anomalies (CUA) may worsen defective placentation, but the predictive value of angiogenic biomarkers in this high-risk group is unclear. Objective: To evaluate serum soluble fms-like tyrosine kinase-1 (sFlt-1), placental growth factor (PlGF), the sFlt-1/PlGF ratio and uterine artery pulsatility index (UtA-PI) for predicting early- and late-onset preeclampsia (PE) in CUA pregnancies. Methods: This prospective longitudinal cohort included 145 women with CUA and 290 age-, parity- and BMI-matched controls at two Indonesian tertiary hospitals. Participants were assessed at 11–14, 20–24 and 28–32 weeks. PE was defined using ISSHP criteria. Analyses included risk ratios, multivariable logistic regression and receiver-operating-characteristic curves. Results: PE incidence was 19.3% in CUA versus 5.9% in controls (RR 3.29, 95% CI 1.87–5.82; p < 0.001); early-onset PE occurred in 8.3% versus 1.4% (RR 6.00; p < 0.001). At 20–24 weeks, the sFlt-1/PlGF ratio was higher in CUA pregnancies that developed PE (42.5 vs 14.2; p < 0.001) and independently predicted PE (adjusted OR 2.72 per SD, 95% CI 1.58–4.69). The ratio-plus-UtA-PI model predicted early-onset PE with an AUC of 0.89 (95% CI 0.84–0.93), sensitivity of 88.1% and NPV of 99.3%. Conclusion: The mid-trimester sFlt-1/PlGF ratio combined with UtA-PI strongly predicted early-onset PE in CUA. Pending external validation, its high NPV may support targeted surveillance in this under-studied population.